2018
DOI: 10.1007/s00011-018-1158-3
|View full text |Cite
|
Sign up to set email alerts
|

Genes and their single nucleotide polymorphism involved in innate immune response in central nervous system in bacterial meningitis: review of literature data

Abstract: BackgroundThere are many studies analysing the effect of SNPs in genes coding proteins which are involved in innate immune response on susceptibility to invasive bacterial disease. Many of them gave inconclusive results. Regarding the complexity of immune response and cooperation between particular elements, number of SNPs may have a cumulative effect on the susceptibility to bacterial meningitis.FindingsIn most studies cooccurrence of several SNPs was not analysed. These studies were performed on small groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Together, these studies suggest a link between host bacterial clearance and disease severity due to a dysregulated host inflammatory response in mice with disrupted TLR2/4 signalling. Consistent with this, single nucleotide polymorphisms (SNP) of genes responsible for bacterial sensing and their associated downstream signalling have been implicated in the prognosis of, and susceptibility to, bacterial infections 19,20 . While TLR2 + 2477 G/A polymorphism is linked to heightened risk of pneumococcal meningitis 21 , pneumococcus-infected persons with certain SNP in TLR4 are at increased risk of developing invasive diseases 22 .…”
Section: Introductionmentioning
confidence: 74%
“…Together, these studies suggest a link between host bacterial clearance and disease severity due to a dysregulated host inflammatory response in mice with disrupted TLR2/4 signalling. Consistent with this, single nucleotide polymorphisms (SNP) of genes responsible for bacterial sensing and their associated downstream signalling have been implicated in the prognosis of, and susceptibility to, bacterial infections 19,20 . While TLR2 + 2477 G/A polymorphism is linked to heightened risk of pneumococcal meningitis 21 , pneumococcus-infected persons with certain SNP in TLR4 are at increased risk of developing invasive diseases 22 .…”
Section: Introductionmentioning
confidence: 74%
“…We recently reported that Finnish adults who are carriers of the variant genotypes of this TLR4 SNP had significantly lower concentrations of serum IL-6, IL-12, and IL-17A than those who are carriers of the wild-type of TLR4 [40]. It is known that TLR4 variants are associated with hypo-responsiveness to LPS, and humans with these polymorphisms are more susceptible to infections caused by Gram-negative bacteria, and the disease is often more severe [10]. One study found a connection between TLR4 SNPs and invasive pneumococcal sepsis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal nasopharyngeal carriage is common in the general population and affects people of all ages. S. pneumoniae causes the most severe disease in both young and old people [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for a role of CB2 deficiency as a risk factor for bacterial infection of the CNS is lacking so far. A review paper by Gowin and colleagues (Gowin and Januszkiewicz-Lewandowska, 2018) inventoried SNPs involved in bacterial meningitis, but CB2-related SNPs were not reported.…”
Section: Discussionmentioning
confidence: 99%